PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VB SD NEGERI 004 BAGAN TIMUR - Julia Sari; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted to determine the learning outcome of students by implementing Direct Learning. This research was done in class VB SD Negeri 004 Bagan Timur. This research is a classroom action research conducted in two cycles of planning, implementation, observation and reflection. The data collected in this study is teacher's activities, student activities and the student learning outcomes. Data were collected using a written test and observation sheet. The results of the analysis and discussion show the teacher activity, student activity and learning outcomes have increased. Teacher activity increased, in the first cycle of the first meeting the average percentage of teacher activity was 85.00% (good) increased to 90.00% (excellent) at the second meeting and increased again in cycle II fourth and fifth meeting to 100, 00% (excellent). Student activity increased, in cycle I first meeting average percentage of student activity 70.00% (good) increased to 80.00% (good) at the second meeting and increased again in cycle II fourth meeting to 85.00% (good ) and the fifth meeting becomes 90.00% (excellent). The learning outcome increased from the basic score of 64.00% (less) to 74.67% (enough) in cycle I and increased again to 81.50% (good) in cycle II. Students classical completeness in the first cycle of 76.67% (complete) increased to 90.00% (complete) in cycle II. It can be concluded that the application of direct learning can improve learning outcomes grade science students VB SD Negeri 004 Bagan Timur.Keywords: Direct Learning, Learning outcomes